2021
DOI: 10.3389/fcimb.2021.604117
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis-HIV Coinfection as a Predictor of Increased Leishmania Transmission at the Village Level in Bihar, India

Abstract: BackgroundVisceral leishmaniasis (VL) is on the verge of being eliminated as a public health problem in the Indian subcontinent. Although Post-kala-azar dermal leishmaniasis (PKDL) is recognized as an important reservoir of transmission, we hypothesized that VL patients co-infected with Human Immunodeficiency Virus (HIV) may also be important reservoirs of sustained leishmania transmission. We therefore investigated to what extent cases of PKDL or VL-HIV are associated with VL incidence at the village level in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…As the effort to eliminate VL as a public health problem has progressed substantially in the ISC, the proportion of patients with VL-HIV has increased both in absolute numbers and as a proportion of all VL cases. Indeed, a more recent analysis of the epidemiological spread and impact of VL-HIV has suggested that the presence of VL-HIV cases was associated with a greater than two-fold increase in VL incidence at the village level, with an incidence risk ratio similar to that of post kala-azar dermal leishmaniasis (PKDL) [ 13 ]. As such, establishing the scale of asymptomatic infections in HIV patients may contribute significantly to improved programmatic policy in sustaining elimination targets.…”
Section: Introductionmentioning
confidence: 99%
“…As the effort to eliminate VL as a public health problem has progressed substantially in the ISC, the proportion of patients with VL-HIV has increased both in absolute numbers and as a proportion of all VL cases. Indeed, a more recent analysis of the epidemiological spread and impact of VL-HIV has suggested that the presence of VL-HIV cases was associated with a greater than two-fold increase in VL incidence at the village level, with an incidence risk ratio similar to that of post kala-azar dermal leishmaniasis (PKDL) [ 13 ]. As such, establishing the scale of asymptomatic infections in HIV patients may contribute significantly to improved programmatic policy in sustaining elimination targets.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors such as climate change involving alterations in temperature, deforestation, natural disasters and poor socio-economic factors, also contribute to the spread of this disease. Due to geographical overlap, malaria-VL co-infections occur in large populations; it is common in East African countries where malaria and VL are co-endemic [17,18]. Drug resistance, organ transplantation and immunosuppression by HIV-1 contribute to the spread of Leishmaniasis [19].…”
Section: Life Cycle Of Leishmaniamentioning
confidence: 99%
“…Anti-leishmanial drugs also showed high toxicity in HIV coinfected VL cases [ 17 , 21 ]. Overall, Leishmania –HIV coinfection poses challenges to the VL control effort [ 3 , 22 , 23 ]. Despite efforts made to identify a new combination of treatments to control the disease, VL with and without HIV coinfection continues to pose a challenge.…”
Section: Introductionmentioning
confidence: 99%